Assimilating FY-4B AGRI Three Water Vapor Channels in Operational Shanghai Typhoon Model (SHTM) Using GSI-Based 3-DVar Approach - Zeyi Niu; Lei Zhang; Yuhua Yang; Yang Han; Hong Li; Dongliang Wang; Wei Huang; Fuzhong Weng (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
This study conducts a one-month parallel experiment to compare the results of the operational Shanghai Typhoon Model with (WV123) and without (CTL) the assimilation of clear-sky brightness temperature from three Fengyun-4B (FY-4B) Advanced Geostationary Radiation Imager (AGRI) water-vapor (WV) channels. The results demonstrate a notable improvement (∼3%) in the moisture fields by the WV123 experiment at all atmospheric levels in the forecasts of 24–120 h when compared to those of the CTL experiment. Besides, results show an improvement in the correlation coefficient of the 500-hPa temperature field from WV123 experiment than CTL experiment after 24 h. For Typhoon Doksuri (2023), the WV123 experiment shows a reduction of 19.4% in the mean track errors after 24-h and an improvement of approximately 10% in the forecasted intensities with five different initial forecasting times. In the cases of Typhoons Mawar, Khanun, and Kaihui in 2023, track errors also exhibit some degree of amelioration in forecast experiments at different initial forecasting times. Moreover, the WV123 experiment can improve the forecast accuracy for precipitation exceeding 250 mm in terms of both spatial distribution and intensity. A statistical study over one-month period indicates that the WV123 experiment shows a relatively neutral impact on the precipitation forecasts of 0–48 h. However, for the forecast lead time of 48–120 h, there is a considerable improvement in terms of the threat scores of predicting the precipitation exceeding 50 mm, suggesting the positive effects of assimilating clear-sky and future all-sky FY-4B AGRI WV radiances.